2004
DOI: 10.1097/01.prs.0000142419.40722.c6
|View full text |Cite
|
Sign up to set email alerts
|

Ventral Rectus Fascia Closure on Top of Mesh Hernia Repair in the Sublay Technique

Abstract: Sublay prosthetic herniorrhaphy has become a widely accepted procedure for incisional hernias. To evaluate the effect of fascia closure on top of mesh repair on infection, and the recurrence rate, the authors reviewed their data regarding herniorrhaphy in the sublay technique. This study was a retrospective analysis of 175 consecutive patients who underwent hernia repair by implantation of prostheses by means of the Stoppa-Rives technique from December of 1994 to December of 2001. All 175 patients had the mesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…This option has the advantage of avoiding placement of the mesh subcutaneously without any fascial covering, leading to high risk of infection. Petersen et al [ 22 ] demonstrated the importance of closure of the rectus sheath ventral to the prosthesis during the retromuscular repair of incisional hernias. He found that the risk of deep prosthetic infection in patients in which it was not possible to close the rectus sheath above was 13 times higher than patients who received closure over the mesh.…”
Section: Discussionmentioning
confidence: 99%
“…This option has the advantage of avoiding placement of the mesh subcutaneously without any fascial covering, leading to high risk of infection. Petersen et al [ 22 ] demonstrated the importance of closure of the rectus sheath ventral to the prosthesis during the retromuscular repair of incisional hernias. He found that the risk of deep prosthetic infection in patients in which it was not possible to close the rectus sheath above was 13 times higher than patients who received closure over the mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Excellent results have been achieved and reported recurrence rates have been less than 1 percent [4]. On the other hand these synthetic materials are physically and chemically inert, induce minimal inflammatory or foreign body reaction, resist mechanical strains, and cause seroma, testicular atrophy, chronic pain, and infection [2,3,6,7]. Avoiding for these complications, biomaterials which includes bioabsorbable polyglycolic acid and self reinforced polyglycolic acid have been developed and used in the experimental and clinical studies [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Various Copyright © 2012 SciRes. SS F. KURT, M. ABEŞ 364 types of prosthetic materials which include polyester, mersilene, prolene, polypropylene, and expanded polytetrafluoroethylene meshes have been developed and commonly used for the reinforcement of the weakened abdominal wall [2,3,5]. Prosthetic materials allow the hernia to be repaired without tension being placed on the surrounding tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a mechanical standpoint, mesh positioned posterior to the fascial defect takes advantage of Pascal's principle of hydrostatics by distributing the intra-abdominal forces over the surface area of the mesh. The retrorectus space or preperitoneal space is a well-vascularized domain where mesh can incorporate with reduced risk of infection (14). Avoidance of mesh placement in the intraperitoneal cavity is attractive to avoid the adhesive potential and possibility of future mesh-related complications (15).…”
Section: Discussionmentioning
confidence: 99%